Jean Truax, Aelred the Peacemaker: The Public Life of a Cistercian Abbot, Cistercian Studies Series 251, Collegeville MI 2017, Cistercian Publications – Liturgical Press, ss. 325. - Groń, Ryszard (Vox Patrum, 2018)
nie dotyczy